International faculty member’s perceived Professional Learning and Development (PLD) experiences at a Japanese university : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Teaching and Learning at Massey University, New Zealand - Ju, Lucia Sunyoung (Massey University, 2024)
This thesis examines international faculty members’ (IFM) current perceptions of professional learning and development (PLD) in Japanese universities. Recent internationalisation initiatives by the Japanese government involved hiring faculty members from overseas to become agents of change. These faculty members are tasked with introducing new educational theories and pedagogy and engaging in research. However, IFM encountered challenges in integrating into Japanese universities due to language barriers, cultural misunderstandings and work-related factors. To gain a comprehensive understanding of the current situation of PLD for IFM, data were collected via semi-structured interviews with eight IFM across universities in Japan. The data were analysed using Braun and Clark’s (2006) six phases of thematic analysis. The analysis showed the alignment between the factors that impeded IFM’s integration into Japanese universities and their limited participation in PLD. Nonetheless, IFM recognised the importance of communication and engagement in PLD and actively sought learning opportunities. Currently, there is little to no published work about IFM’s perception of PLD in Japanese universities. Therefore, a key strength of this study was that it could serve as a base for future studies that investigate IFM’s perceptions of PLD in other East Asian countries and IFM new to the teaching profession, women IFM involvement in Japanese universities and IFM’s perceptions of specific PLD (i.e., peer observation, feedback etc.)
Keywords: professional learning and development; international faculty; integration; internationalisation; Japanese university; higher education; 390303 Higher education